Design and optimization of millimeter-scale electroadhesive grippers. (31st July 2020) - West, Jared D; Mici, Joni; Jaquith, Jeffrey F; Lipson, Hod
Abstract: Electroadhesion is a complex physical phenomenon often used for astrictive prehension of a wide range of materials. Particularly effective at grasping millimeter-scale objects, electroadhesion is increasingly relevant to robotics, automation, and electronics manufacturing. This work presents a generalized optimization strategy and experimental validation of two-dimensional electroadhesors for gripping of millimeter-scale objects utilizing sub-millimeter-scale design parameters. Numerical electroadhesor optimization was based on three-dimensional electrostatic field simulations in COMSOL Multiphysics while experimental validation was performed through the gripping of incrementally increasing weights. Simulations and experiments were designed for the electroadhesion of objects with 1.6 mm thickness and using an applied voltage differential of 600 V. The spacings between electroadhesor pads and the width of the pads were varied to determine optimal parameters. To generalize results as much as possible, optimal values for each parameter are expressed as a ratio of pad area to the bounding box area of the electroadhesive element; the optimal electroadhesor pad spacing has been shown to be 0.5 mm and the optimal ratio has been shown to be 0.75 for both conductive and insulating objects of 1.6 mm thickness. Having determined the optimal design parameters, we present a step-by-step design methodology for electroadhesive elements intended to grasp both conductive and insulating millimeter-scale objects.